The parable of the Feast (Lk 14:16b–23): Breaking down boundaries and discerning a theological–spatial justice agenda - Eck, Ernest Van (HTS teologiese studies, 2016)
The parable of the Feast (Lk 14:16b–23) is perhaps the example par excellence in the New Testament that addresses spatial justice and reconciliation. In the parable, Jesus advocates for the eradication of all boundaries linked to the social–economic status of the marginalised. The parable argues, from a social justice perspective, that there is no such thing as privileged space; priviliged space, on the contrary, builds boundaries. The reading of the parable presented critically engages with real-life experiences of marginalised people living on the periphery of the city and the boundaries that are created by megachurches in their close surroundings.